Psychological Determinants and Mediating Mechanisms of Muslim Consumers’ Intention to Boycott Israeli Products - Amalia, Hani Khairo; Masruroh, Amalia; Prasetyo, Ari (Universitas Airlangga, 2025)
This study investigates the psychological determinants influencing Muslim consumers’ intention to boycott Israeli products, focusing on the roles of animosity, perceived efficacy, and subjective norms, as well as the moderating effects of celebrity trend-setters and skeptical opinions. Using a quantitative approach, data were collected through an online survey of 172 Muslim respondents in Surabaya, selected via purposive sampling. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was employed to test the proposed hypotheses. The results show that animosity and perceived efficacy significantly and positively influence boycott intention, while subjective norms have no direct effect. Instead, the influence of subjective norms is mediated by animosity and perceived efficacy, highlighting the emotional and cognitive pathways through which social pressure shapes boycott participation. This study provides contextual evidence from Muslim consumers in Surabaya, thereby broadening the geographical and cultural scope of boycott research and enhancing the generalizability of psychological theories of boycott intention within the Southeast Asian Muslim context. Although the moderating effects of celebrity trend-setters and skeptical opinions were not statistically significant, their inclusion advances the boycott literature by integrating contemporary constructs of psychological and social influence that have been rarely explored empirically. These findings underscore the evolving nature of consumer behavior in socially and politically charged contexts, suggesting that future studies further investigate how media credibility, consumer trust, and moral conviction interact to drive or inhibit collective ethical action. From a managerial perspective, the study emphasizes that companies involved in sensitive geopolitical or ethical issues should prioritize transparent communication, ethical branding, and value-driven corporate responsibility to maintain consumer trust and mitigate reputational risks.